2020
DOI: 10.3390/ijms21218091
|View full text |Cite
|
Sign up to set email alerts
|

p53 Immunohistochemical Patterns in HPV-Independent Squamous Cell Carcinomas of the Vulva and the Associated Skin Lesions: A Study of 779 Cases

Abstract: Human papillomavirus (HPV)-independent vulvar squamous cell carcinomas (VSCC) and its precursors frequently harbour TP53 mutations. Recently, six p53 immunohistochemical (IHC) patterns have been defined, which have shown strong correlation with TP53 mutation status. However, few studies have applied this new six-pattern framework and none of them exhaustively compared p53 IHC positivity and patterns between invasive VSCC and adjacent skin lesion. We performed p53 IHC in a series of 779 HPV-independent VSCC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 37 publications
3
34
0
1
Order By: Relevance
“…p53-wild-type pattern, i.e., scattered, heterogeneous, basal/para-basal expression, is primarily seen in nondysplastic lesions. However, this pattern has been also occasionally observed in dVIN [15,[20][21][22][23]. Hence, a p53-wild-type pattern does not preclude a histological diagnosis of dVIN.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…p53-wild-type pattern, i.e., scattered, heterogeneous, basal/para-basal expression, is primarily seen in nondysplastic lesions. However, this pattern has been also occasionally observed in dVIN [15,[20][21][22][23]. Hence, a p53-wild-type pattern does not preclude a histological diagnosis of dVIN.…”
Section: Methodsmentioning
confidence: 89%
“…This is in line with recent literature, which states that 17–42% cases of dVIN can show wild-type p53-expression [ 4 ], and implies that p53-IHC may not effectively inform the diagnosis in every case of dVIN. Furthermore, p53-IHC patterns in VSCC and the adjacent dVIN may not show perfect concordance [ 22 ]. A recent study reported that while dVIN adjacent to p53-wild-type VSCC always shows wild-type p53-expression, dVIN adjacent to p53-mutant VSCC can show wild-type p53-expression in 31.4% of cases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant patterns of p53-expression are used to support a histological diagnosis of dVIN, as these have been reported to reflect TP53 mutations that characterize dVIN [ 16 , 17 , 18 ]. However, 17–42% of dVIN can show wild-type p53-expression, which is usually observed in non-dysplastic lesions [ 19 , 20 , 21 , 22 ]. Furthermore, recent research has identified a novel putative precursor of HPV-independent VSCC, named differentiated exophytic vulvar intraepithelial lesion (de-VIL) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the oropharyngeal region is usually the most frequently associated with HPV infection, SCC affects other regions, such as the lip and the tongue, have been associated with this viral infection in up to 37% [5]. Interestingly, types 16 and 18 HPV are usually related to this type of tumor, as it happens in cervical cancers [6,7]. HPV 16 accounts for 90% of cases.…”
Section: Introductionmentioning
confidence: 99%